2020
DOI: 10.1007/s10439-020-02484-2
|View full text |Cite
|
Sign up to set email alerts
|

Determining Haemodynamic Wall Shear Stress in the Rabbit Aorta In Vivo Using Contrast-Enhanced Ultrasound Image Velocimetry

Abstract: Abnormal blood flow and wall shear stress (WSS) can cause and be caused by cardiovascular disease. To date, however, no standard method has been established for mapping WSS in vivo. Here we demonstrate wide-field assessment of WSS in the rabbit abdominal aorta using contrast-enhanced ultrasound image velocimetry (UIV). Flow and WSS measurements were made independent of beam angle, curvature or branching. Measurements were validated in an in silico model of the rabbit thoracic aorta with moving walls and pulsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Importantly, as a measure of pulsatility, RRI reflects intrinsic renal artery compliance but is also influenced substantially by changes in upstream systemic and downstream intrarenal vascular properties [26]. The elevated RRI is thus consistent with the increased aortic PWV observed in this present study but suggests that the decline in renal artery compliance is delayed compared with changes in the ascending aorta and aortic arch where hydrostatic and shear forces are greater [59]. Oxidative stress [27,47], impaired nitric oxide generation [6], and inflammatory mechanisms [60] have been implicated in vascular changes during fructose and high-salt exposure.…”
Section: Discussionsupporting
confidence: 86%
“…Importantly, as a measure of pulsatility, RRI reflects intrinsic renal artery compliance but is also influenced substantially by changes in upstream systemic and downstream intrarenal vascular properties [26]. The elevated RRI is thus consistent with the increased aortic PWV observed in this present study but suggests that the decline in renal artery compliance is delayed compared with changes in the ascending aorta and aortic arch where hydrostatic and shear forces are greater [59]. Oxidative stress [27,47], impaired nitric oxide generation [6], and inflammatory mechanisms [60] have been implicated in vascular changes during fructose and high-salt exposure.…”
Section: Discussionsupporting
confidence: 86%
“…A purpose-written 2-D echo-particle image velocimetry (echo-PIV) algorithm was used to track the local displacement of scatterers in two consecutive images; coupled with the known time difference between the images, a velocity field could be calculated. The algorithm employed an iterative window deformation cross-correlation method ( Leow and Tang 2018 ; Riemer et al 2020a ). In three iterations, the interrogation window size was halved, from 32 to 8 pixels with an overlap of 50%.…”
Section: Methodsmentioning
confidence: 99%
“…Plane wave contrast-enhanced ultrasound image velocimetry (CEUIV) correlates microbubble speckle patterns in consecutive B-mode images. High-frame-rate (HFR) CEUIV has been reported to accurately measure velocities near the moving arterial wall ( Kim et al 2004 ; Zhang et al 2011 ; Poelma et al 2012 ), and CEUIV can be used to estimate WSS accurately in 2-D ( Gates et al 2018 ; Leow and Tang 2018 ; Riemer et al 2020a ) and 3D ( Riemer et al 2020b ). The use of microbubbles is particularly advantageous in regions where the blood signal is weak or the blood has a velocity similar to that of tissue.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques have been challenging in experimental animal models so far, but recent progress in the development of preclinical imaging approaches has expanded their application [ 18 ]. Riemer et al used contrast-enhanced ultrasound image velocimetry in rabbits and demonstrated the feasibility of spatiotemporal WSS mapping [ 19 ]. Riedl et al computed WSS from 17.6 Tesla MRI data that were longitudinally collected at different sites of the aorta from ApoE knockout mice fed with a Western-type diet, demonstrating that low WSS was associated with an increased local plaque burden [ 20 ].…”
Section: Experimental Animal Models To Investigate the Role Of Hemodynamics In Atherogenesismentioning
confidence: 99%